A arte da improvisação de Nelson Faria: influências na pedagogia da música popular brasileira - Felipe Boabaid Guerzoni (2014)
Until the 1990s, the process of musical improvisation in the field of brazilian popular music occurred predominantly intuitively. In this scenario, Nelson Faria published the first book about the subject in Brazil changing the prevailing concept of time. Search this research is to investigate the processes of improvisation systematized by the author as well as relating the decline of this practice occurred in Western Europe with the reality of Brazilian Universities.